Філософія інклюзивного туризму - Яріко, Мирослава Олексіївна (ХДАК, 2017)
Розглянуто причини формування інфраструктури інклюзивного туризму, виявлено взаємозв’язок між розвитком інфраструктури, якістю існування фізично або розумово неповносправних людей у суспільстві та типами світогляду. Описано заходи, спрямовані на збільшення рівня інтеграції та міжособистісних комунікацій у суспільстві. Означено дві тенденції, які нині є домінуючими в ставленні до особистості. Показано точки взаємовпливу світського та релігійного типів світоглядів. Окремо висвітлено роль реколекцій для соціальної інтеграції фізично або розумово неповносправних людей.

This paper presents the causes the establishment of inclusive tourism infrastructure. It shows the relationship between the development of the appropriate infrastructure, the quality of the existence of physically and mentally disabled people in society and types of worldview. The author describes the measures aimed at increasing the level of social integration and interpersonal communication in the society. The author indicates two trends, which are dominant in the context of the relationship to the person today. The points of intersection and interference of secular and religious types of worldviews are shown. The article is specifically concerned with the role of spiritual exercises for the social integration of physically and mentally disabled people.
Keywords: інклюзивний туризм; inclusive tourism